2007
DOI: 10.1016/j.ydbio.2007.08.053
|View full text |Cite
|
Sign up to set email alerts
|

Sulfs are regulators of growth factor signaling for satellite cell differentiation and muscle regeneration

Abstract: Heparan sulfate proteoglycans (HSPGs) are required during muscle regeneration for regulating extracellular signaling pathways. HSPGs interact with growth factors and receptors through heparan sulfate (HS) chains. However, the regulatory mechanisms that control HS sulfation to affect the growth factor-dependent proliferation and differentiation of satellite cells are yet unknown. Here we report the essential functions of extracellular HS 6-O-endosulfatases (Sulfs) during muscle regeneration. We show that quiesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
56
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 36 publications
5
56
0
Order By: Relevance
“…In contrast, double knock-out mice showed neonatal lethality associated with subtle skeletal abnormalities and kidney hypoplasia (20,28,29). Defects in esophageal innervation, muscle regeneration, and spermatogenesis were also reported in Sulf1/2 double knock-out mice (20,30,31). Recently, by using Sulf1/2 double knock-out mice that survived to adulthood (probably due to differences in genetic background), it was reported that aged double knockout mice developed proteinuria and showed abnormal renal morphology (32).…”
mentioning
confidence: 99%
“…In contrast, double knock-out mice showed neonatal lethality associated with subtle skeletal abnormalities and kidney hypoplasia (20,28,29). Defects in esophageal innervation, muscle regeneration, and spermatogenesis were also reported in Sulf1/2 double knock-out mice (20,30,31). Recently, by using Sulf1/2 double knock-out mice that survived to adulthood (probably due to differences in genetic background), it was reported that aged double knockout mice developed proteinuria and showed abnormal renal morphology (32).…”
mentioning
confidence: 99%
“…Both Sulf1 and Sulf2 are endosulfatases that act extracellularly and generate structural heterogeneity along HS chains by modifying the sulfation pattern of HS postsynthetically. Sulf1/ Sulf2 double null mutant mice show numerous distinct phenotypes (31)(32)(33)(34)(35)(36)(37). In skeletal structures, malformations, including reduced bone length, premature vertebrae ossification, and fusion of sternebrae and tail vertebrae, are observed (35).…”
mentioning
confidence: 99%
“…As mentioned, previous studies have investigated the effects of reduction of SULF1 and SULF2 in abnormal embryonic development [15][16][17]. Therefore, we hypotheses that SULFs polymorphism may have an effect on recurrent pregnancy losses in RM patients.…”
Section: Discussionmentioning
confidence: 83%
“…It was shown that genetically deficient mice for these sulfatases, show some abnormal phenotypes such as brain malformations, skeletal malformations, abnormal innervations of smooth muscle and embryonic lethality [15][16][17]. In one study mice were generated carrying loss of function alleles for the secreted Sulf1 and Sulf2.…”
Section: Introductionmentioning
confidence: 99%